2012
DOI: 10.1111/desc.12008
|View full text |Cite
|
Sign up to set email alerts
|

Language is not necessary for color categories

Abstract: The origin of color categories is under debate. Some researchers argue that color categories are linguistically constructed, while others claim they have a pre-linguistic, and possibly even innate, basis. Although there is some evidence that 4-6-month-old infants respond categorically to color, these empirical results have been challenged in recent years. First, it has been claimed that previous demonstrations of color categories in infants may reflect color preferences instead. Second, and more seriously, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Other studies claimed the inverse, namely that linguistic categories result from the categorical nature of colour perception. They found that colour vision itself is inherently categorical (Regier, Kay, & Khetarpal, 2007), and that colour categories already exist in infancy before language acquisition (Bornstein, Kessen, & Weiskopf, 1976;Franklin, Clifford, Williamson, & Davies, 2005;Franklin & Davies, 2004;Franklin, Drivonikou, Bevis, et al, 2008;Franklin, Drivonikou, Clifford, et al, 2008;Franklin, Pilling, & Davies, 2005;Ozturk, Shayan, Liszkowski, & Majid, 2013;Skelton, Catchpole, Abbott, Bosten, & Franklin, 2017). Still other findings did not find categorical patterns in colour perception and contradicted the idea of categorical perception (Bachy et al, 2012; A. M. Brown, Lindsey, & Guckes, 2011;Cropper, Kvansakul, & Little, 2013;Davidoff, Goldstein, Tharp, Wakui, & Fagot, 2012;Gerhardstein, Renner, & Rovee-Collier, 1999;Grandison et al, 2016;Kay & Kempton, 1984; Misconceptions about colour categories 8 al., 2010; Roberson, Hanley, & Pak, 2009;Webster & Kay, 2012;Witzel & Gegenfurtner, 2011.…”
Section: Contradictory Empirical Evidencementioning
confidence: 98%
“…Other studies claimed the inverse, namely that linguistic categories result from the categorical nature of colour perception. They found that colour vision itself is inherently categorical (Regier, Kay, & Khetarpal, 2007), and that colour categories already exist in infancy before language acquisition (Bornstein, Kessen, & Weiskopf, 1976;Franklin, Clifford, Williamson, & Davies, 2005;Franklin & Davies, 2004;Franklin, Drivonikou, Bevis, et al, 2008;Franklin, Drivonikou, Clifford, et al, 2008;Franklin, Pilling, & Davies, 2005;Ozturk, Shayan, Liszkowski, & Majid, 2013;Skelton, Catchpole, Abbott, Bosten, & Franklin, 2017). Still other findings did not find categorical patterns in colour perception and contradicted the idea of categorical perception (Bachy et al, 2012; A. M. Brown, Lindsey, & Guckes, 2011;Cropper, Kvansakul, & Little, 2013;Davidoff, Goldstein, Tharp, Wakui, & Fagot, 2012;Gerhardstein, Renner, & Rovee-Collier, 1999;Grandison et al, 2016;Kay & Kempton, 1984; Misconceptions about colour categories 8 al., 2010; Roberson, Hanley, & Pak, 2009;Webster & Kay, 2012;Witzel & Gegenfurtner, 2011.…”
Section: Contradictory Empirical Evidencementioning
confidence: 98%
“…Clifford et al 2009;Franklin and Davies 2006;Ozturk et al 2013, for infants, and Clifford et al 2011, 2012; Ö zgen and Davies 2002, but also Witzel and Gegenfurtner 2013, for adults). The phenomenon can be more precisely characterized as enhanced discrimination of perceptually equidistant stimulus pairs in some regions of the perceptual color space compared to other regions.…”
Section: Some Qualificationsmentioning
confidence: 99%
“…The mere addition of colour to an otherwise monochrome DIG leads to increased understanding (Antúnez et al, 2015). This is likely to be because colours, unlike numbers, are processed innately (Ozturk, Shayan, Liszkowski, & Majid, 2013) and unconsciously (Ro, Singhal, Breitmeyer, & Garcia, 2009). Similarly, symbols have been found to help people differentiate healthy and unhealthy foods (Feunekes, Gortemaker, Willems, Lion, & van den Kommer, 2008;Maubach et al, 2014).…”
Section: Combined Effects Of Nutrition Informationmentioning
confidence: 99%